A correlation of serum fibroblast growth factor 21 level with inflammatory markers and indicators of nutritional status in patients with inflammatory bowel disease - Łukawska, Agata; Mulak, Agata (Frontiers in Physiology, 2024)
Background: Fibroblast growth factor 21 (FGF21) is a stress-inducible hormone that regulates nutrient and metabolic homeostasis. Inflammatory state is one of the stimulators of FGF21 secretion. The aim of the study was to assess a correlations between serum FGF21 level and inflammatory markers as well as nutritional status indicators in patients with inflammatory bowel disease (IBD).Methods: Fasting serum FGF21 level was measured using ELISA test in 105 IBD patients and 17 healthy controls. There were 31 subjects with active ulcerative colitis (UC), 16 with inactive UC, 36 with active Crohn's disease (CD), and 22 with inactive CD. Clinical and endoscopic activity of IBD was evaluated based on validated scales and indices. Fecal calprotectin, serum CRP, and selected parameters of nutritional status were tested in all patients.Results: Serum FGF21 level was characterized by fluctuations depending on the IBD activity. FGF21 level was significantly higher in both active UC and CD compared to inactive phases of the diseases and to the controls. A correlation between FGF21 and fecal calprotectin levels was also found in UC and CD. Additionally, in CD, FGF21 level positively correlated with CRP level. In both UC and CD, a negative correlation was noted between FGF21 level and nutritional status parameters including cholesterol, protein, albumin levels, and BMI.The intensity of intestinal inflammation is related to FGF21 level, which correlates negatively with nutritional status indicators in IBD. The disturbances in FGF21 secretion may contribute to the multifactorial pathogenesis of malnutrition and weight loss in IBD patients.